PENGEMBANGAN MODUL PEMBELAJARAN IPA TERPADU BERWAWASAN SAINS, LINGKUNGAN, TEKNOLOGI DAN MASYARAKAT - Parmin, Parmin (Jurnal Penelitian Pendidikan, 2012)
The research objective to develop an Integrated Science course module minded Science, Environment, Technology and Society. Module develop feasible by experts, students when learning showed good activity and positive impact on the control modul learning materials. The inference module compiled research that effectively used in learning.